Remediation of crude oil contaminated kaolin by adsorption using solid-liquid two-phase partitioning - Peyda, Mazyar (2012)
Soil contamination by crude oil is a major environmental and health hazard. The main goal of this research was to investigate the applicability of using a solid-liquid two-phase partitioning bioreactor (TPPB) to remediate crude oil contaminated kaolin. To achieve this objective, sorption studies were carried out on kaolin contaminated by crude oil using commercial thermoplastic polyurethane (Desmopan®) and 2-propanol as a mobilizing agent followed by bio-regeneration of crude oil loaded polymer beads in the TPPB. The equilibrium sorption capacity (qe) as well as the kinetic behaviour of the thermoplastic polyurethane (TPU) was determined as a function of the crude oil dilution with 2-propanol. The polymeric sorbent exhibited the highest qe value when immersed in a 50% diluted crude oil. The sorption experimental data correlated well with different kinetic models. The Elovich kinetic model correlated accurately with the diluted crude oil experimental data; while the pseudo-first order and pseudo-second order kinetic models could also predict the sorption of n-alkanes (C14-C36) and polycyclic aromatic hydrocarbons (PAHs) into the polymeric sorbent, respectively. Parameters of the power law model showed that the mechanism of transport for both diluted and undiluted-crude oil into the TPU was Fickian. The sorption kinetics of the PAHs and the short-chain n-alkanes (C14-C18) were also shown to be a direct function of their octanol/water partitioning coefficient. In contrast, the sorption rates of the long chain n-alkanes (C20-C36) were inversely associated with their molecular volumes. Finally, intraparticle diffusion analysis indicated that the 2-propanol present in crude oil had reduced both the external and the internal mass transfer resistances within the internal structure of the TPU. A central composite design (CCD) under response surface methodology (RSM) was employed for experimental design in kaolin remediation study and analysis of the results. The influences of independent variables on the total petroleum hydrocarbon (TPH) reduction efficiency were determined using a statistically significant quadratic model. Remediation was more efficient when the ratio of the mobilizing agent to the kaolin was equal to 3.00 mL g-1. The results exhibited that the interaction between the extraction phase ratio and the initial concentration of crude oil in kaolin had significantly influenced the TPH removal. Bio-regeneration of crude oil loaded TPU was optimized in a solid-liquid TPPB by applying a RSM based D-optimal design. The bacterial strains in the consortium were identified as Brevibacillus brevis, Gordonia sp., Ochrobactrum anthropic, Cellulosimicrobium terreum, and Bacillus sp through analysis of the 16S rRNA gene. Optimum combinations of key factors with a statistically significant cubic model were used to maximize iodegradation in the TPPB. The validity of the model was successfully verified by the agreement between the model-predicted results and the experimental results. The bio-regeneration studies in a 5L reactor showed a significant reduction (72.07±0.63%) of low molecular weight (2-3 ring) PAHs and nalkanes (97.75±0.26%) present in the crude oil loaded solid polymers. Regeneration and reusability of the crude oil loaded TPU were also confirmed by subjecting the sorbent to successive sorption-regeneration cycles in the TPPB. These findings show that solid polymer extraction followed by bio-regeneration of sorbents in a TPPB is applicable to treat crude oil contaminated kaolin.